Ventriculoperitoneal shunt insertion for hydrocephalus in human immunodeficiency virus-infected adults: a systematic review and meta-analysis protocol - James J. M. Loan; Ncedile Mankahla; Graeme Meintjes; A. Graham Fieggen (Systematic Reviews, 2017)
Abstract Background Hydrocephalus is a recognised complication of human immunodeficiency virus (HIV)-related opportunistic infections. Symptomatic raised cerebrospinal fluid pressure can be treated with ventriculoperitoneal shunt insertion (VPS). In HIV-infected patients however, there is a concern that VPS might be associated with unacceptably high rates of mortality. We aim to systematically review and appraise published literature to determine reported outcomes and identify predictors of outcome following VPS in relevant subgroups of HIV-infected adults. Methods The following electronic databases will be searched: The Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (PubMed), EMBASE, CINAHL (EBSCOhost), LILACS (BIREME), Research Registry ( www.researchregistry.com ), the metaRegister of Controlled Trials (mRCT) ( www.controlled-trials.com ), ClinicalTrials.gov ( www.clinicaltrials.gov ) and OpenSIGLE database. Any randomised studies, cohort studies, case-control studies, interrupted time series or sequential case series reporting survival following VPS in HIV-infected individuals will be included. If high-quality homogenous studies exist, meta-analysis will be conducted to determine 1-, 6- and 12-month mortality with comparison made between underlying aetiologies of hydrocephalus. Discussion and conclusion This study will generate a comprehensive review of VPS in HIV-infected patients for publication. The primary outcome of meta-analysis is 12-month survival. If only low-quality, heterogeneous studies are available, this study will demonstrate this deficiency and will be of value in justifying and aiding the design of future studies. Systematic review registration PROSPERO CRD42016052239